Dinamika Persepsi Keadilan Pajak Pada Wajib Pajak Pemula - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This study aims to explore the dynamics of tax fairness perceptions among novice taxpayers. Using a qualitative descriptive-interpretative approach, the research focuses on how novice taxpayers understand and experience tax fairness during their initial interactions with the tax system. Data were collected through in-depth semi-structured interviews with purposively selected informants and analyzed using an interactive qualitative analysis model. The findings indicate that tax fairness is perceived in a subjective and contextual manner, primarily based on personal experiences rather than formal knowledge of tax principles. Novice taxpayers tend to assess fairness through the perceived burden of taxes and the simplicity or complexity of administrative procedures. Procedural experiences and social environments significantly influence how tax fairness is interpreted. Moreover, the study reveals a gap between formal tax compliance and normative acceptance of tax fairness, suggesting that compliance may occur even when perceptions of fairness are not fully established. These findings highlight the importance of adopting a more empathetic and experience-oriented approach in tax administration to strengthen the long-term legitimacy of the tax system.